Comparative in vitro and in silico analysis of the ability of basic Asp49 phospholipase A2 and Lys49-phospholipase A2-like myotoxins from Bothrops diporus venom to inhibit the metastatic potential of murine mammary tumor cells and endothelial cell tubulogenesis: Asp49 vs Lys49 phospholipases A2: Inhibition of metastasis and angiogenesis - Sasovsky, Daniela Jaqueline (2024)
Snake venoms are a complex mixture of proteins and polypeptides that represent a valuable source of potential molecular tools for understanding physiological processes for the development of new drugs. In this study two major PLA2s, named PLA2-I (Asp49) and PLA2-II (Lys49), isolated from the venom of Bothrops diporus from Northeastern Argentina, have shown cytotoxic effects on LM3 murine mammary tumor cells, with PLA2-II-like exhibiting a stronger effect compared to PLA2-I. At sub-cytotoxic levels, both PLA2s inhibited adhesion, migration, and invasion of these adenocarcinoma cells. Moreover, these toxins hindered tubulogenesis in endothelial cells, implicating a potential role in inhibiting tumor angiogenesis. All these inhibitory effects were more pronounced for the catalytically-inactive toxin. Additionally, in silico studies strongly suggest that this PLA2-II-like myotoxin could effectively block fibronectin binding to the integrin receptor, offering a dual advantage over PLA2-I in interacting with the αVβ3 integrin. In conclusion, this study reports for the first time, integrating both in vitro and in silico approaches, a comparative analysis of the antimetastatic and antiangiogenic potential effects of two isoforms, an Asp49 PLA2-I and a Lys49 PLA2-II-like, both isolated from Bothrops diporus venom.